Um antropólogo no gabinete: Notas sobre etnografia e o trabalho no parlamento - Belisário, Gustavo (Cadernos de Campo (São Paulo, 1991), 2021)
This article discusses the daily work of an anthropologist in parliament. Based on reflections with an ethnographic style on the work experiences in the technical team of District Deputy Fábio Félix (PSOL - DF) in the Legislative Chamber of the Federal District, I discuss the impact of the academic path in anthropology in the production of legislative documents and in the way of facing the political game. The different ways of conceiving political relevance, valuing themes and telling stories are discrepancies that produce strangeness in the anthropologist who works in parliament. In summary, in spite of the differences between making ethnographies and producing laws, facing parliament without taking it so seriously is a possible compromise to keep doing both.